The Effectiveness of Exercise Interventions for the Management of Frailty: A Systematic Review. (1st March 2011) - Theou, Olga; Stathokostas, Liza; Roland, Kaitlyn P.; Jakobi, Jennifer M.; Patterson, Christopher; Vandervoort, Anthony A.; Jones, Gareth R.
Abstract : This systematic review examines the effectiveness of current exercise interventions for the management of frailty. Eight electronic databases were searched for randomized controlled trials that identified their participants as "frail" either in the title, abstract, and/or text and included exercise as an independent component of the intervention. Three of the 47 included studies utilized a validated definition of frailty to categorize participants. Emerging evidence suggests that exercise has a positive impact on some physical determinants and on all functional ability outcomes reported in this systematic review. Exercise programs that optimize the health of frail older adults seem to be different from those recommended for healthy older adults. There was a paucity of evidence to characterize the most beneficial exercise program for this population. However, multicomponent training interventions, of long duration (≥5 months), performed three times per week, for 30–45 minutes per session, generally had superior outcomes than other exercise programs. In conclusion, structured exercise training seems to have a positive impact on frail older adults and may be used for the management of frailty.